Lightness : the inevitable renaissance of minimum energy structures. - Beukers, Adriaan, ....-; van Hinte, Ed, 1951- (Rotterdam : 010, 2005)
Even one-celled organisms already seem to know what mankind is still trying to invent. Recreating lightness with the synergy of different materials is the main theme of this book. It deals with smart combinations of fibres and plastics, with creating efficient shapes and freezing textiles. Lightness contains many examples, good as well as bad. They can be found in industrial design, architecture, bridge constructions, sports equipment and vehicle technology. Among them are a small airplane, a cooling trailer, a bicycle and even a flexible beer container. It will be difficult not to be inspired by what you will read and see.